TREATMENT OF DIARRHOEA USING TRADITIONAL MEDICINES: CONTEMPORARY RESEARCH IN SOUTH AFRICA AND ZIMBABWE - Maroyi, Alfred (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Gastrointestinal disorders, diarrhoea in particular remain a major concern in South Africa and Zimbabwe resulting inhigh mortality rates when left untreated. This investigation was aimed at documenting herbal medicines used in the treatment ofdiarrhoea in South Africa and Zimbabwe.Materials and Methods: A review of literature on plant species used as remedies for diarrhoea in South Africa and Zimbabwe wasundertaken by the use of different electronic databases such as Google Scholar, ScienceDirect, Scopus as well as library searches atthe University of Fort Hare, South Africa and the National Herbarium of Zimbabwe (SRGH) in Harare, Zimbabwe.Results: This study reported ten plant species most widely used to treat diarrhoea in South Africa and Zimbabwe. Of the lot,Sclerocarya birrea (A. Rich.) Hochst. was the most popular medicinal plant used as antidiarrhoeal remedy (11 literature citations) inSouth Africa and Zimbabwe, followed by Elephantorrhiza elephantina (Burch.) Skeels and Schotia brachypetala Sond. with eightliterature citations each. The roots (47.4%) are the most frequently used plant parts, followed by bark (26.3%), leaves (21.1%) andrhizomes (5.3%).Conclusion: The documented antidiarrhoeal activities of this repository of selected plant species against diarrhoea causing agentssuch as rotavirus, Escherichia coli, Shigella, Campylobacter, Giardia, Entamoeba histolytica, Salmonella, Yersinia and Vibriocholerae calls for further investigation aimed at isolating phytochemical compounds responsible for antidiarrhoeal activities, theirmode of action, and also establish their safety and efficacy. This cross-cultural acceptance of antidiarrhoeal herbal medicines and theuse of the same plant species in different geographical zones serve as an indication of the importance of herbal medicines in primaryhealthcare of local communities.